Optimization of Labrasol and Tween 80 in Self Nano-Emulsiying Drug Delivery System (SNEDDS) Mefenamic Acid Using The Simplex Lattice Design Method - Silvy Aldila; Anifatus Sa’adah; Valentina Girsang; Farah Destyana Nurainy; Ummi Kalsum; Rossalina Nurul Agustin; Novita Dwi Dahliyanti (CV. Inara, 2026)
Mefenamic acid is a derivative of anthranilic acid that functions as a nonsteroidal anti-inflammatory drug (NSAID), antipyretic, and analgesic. Mefenamic acid is included in the Biopharmaceutical Classification System (BCS) class II which has low solubility and high permeability. The manufacture of SNEDDS requires a non-ionic surfactant with an HLB (Hydrophilic-Lipophilic Balance) value of more than 10. Mefenamic acid has high solubility in the surfactant Labrasol which has HLB 12 and Tween 80 which has HLB 15. This study aims to develop mefenamic acid into a Self Nano-Emulsifying Drug Delivery System (SNEDDS) with the optimization of labrasol and tween 80 as surfactants. The optimization of mefenamic acid SNEDDS is made using the simplex lattice design method. In the optimization, 6 running SNEDDS formulas were obtained with mefenamic acid. Chemical physics testing includes organoleptic evaluation, pH, viscosity, percent of transmitters, emulsification time, stability, particle size, potential zeta, and level determination. The results showed that the optimal combination of labrasol and tweenat SNEDDS mefenamic acid 80, namely 24% Labrasol and 1% Tween 80, with a desirability value of 0.984, had a clear, non-rancid, homogeneous, liquid-shaped color, pH of 4.69, viscosity 31.33 cP, transmitter percentage 96.80%, emulsification time 29.11 seconds, particle size 44.30 nm, zeta potential -28.87 mV, and a polydispersivity index of 0.563, with a percentage of levels of 100.08%, 100.70%, and 99.87%, respectively. Key words: Self Nano-Emulsifying Drug Delivery System (SNEDDS), Labrasol, Tween 80